Study of the feasibility of mix of species from sawmill waste and limiting for particleboard - Alves, Luciane Simal [UNESP]; Silva, Sérgio Augusto Mello da [UNESP]; Azambuja, Maximiliano dos Anjos [UNESP]; Varanda, Luciano Donizete; Christoforo, André Luis; Gonçalves, Decio; Lahr, Francisco Antonio Rocco (Scientific and Academic Publishing, 2014)
This study aims to determine physical properties of particleboard made of sawmill waste, as a mix of several wood species, and two adhesives: urea-formaldehyde, usually employed in industry (even with drawbacks or formaldehyde emission during pressing) and FASTBOND®, water based resin, still poorly referenced in literature. Sixteen panels have been produced, in four experimental conditions, defined by using two adhesives and a 12 mm thick limiter (or not). Variance analysis was adopted to evaluate influence of experimental conditions on physical properties of produced panels, manufactured in nominal dimensions 350x350mm; 10% resin related to particles mass (at 5% moisture); 3.5 MPa compaction pressure, temperature 130°C, in a 10 min cycle. Tests to determine density, moisture content, swelling and water absorption were carried out based on normative parameters of ABNT NBR 14810:2006. Results have been satisfactory to panels produced with urea-formaldehyde but those manufactured with polychloroprene based resin (FASTBOND®) not meet regulatory requirements. Best results have been obtained without limiter.
Keywords: Particleboards; Wood waste; Physical properties; Analysis of variance